Atividade anticolinesterásica dos óleos essenciais e componentes majoritários de Piper spp e Aniba canelilla e docagem molecular do 1-nitro-2-feniletano - SILVA, Nayla Nunes dos Santos (Universidade Federal do Pará, 2017)
Currently, Alzheimer's disease (AD) is considered a significant public health problem worldwide and the major complication of the disease is the deficit of cholinergic neuron activity, a fact that can be reversed and/or mitigated by raising levels of the neurotransmitter acetylcholine (ACh). The most effective way to increase the available amount of acetylcholine is the inhibition of the acetylcholinesterase enzyme (AChE). In the search for new natural cholinesterasic inhibitors, the essential oils and major components of five aromatic plants occurring in the Amazon region were investigated using the AChE inhibition test by direct bioautography. The oils and major components were obtained from Aniba canelilla (1-nitro-2-phenylethane), P. aduncum (dillapiole), P. callosum (safrole), P. divaricatum (methyleugenol) and P. marginatum (safrole+3,4-methylenedioxipropiophenone). The oils of A. canelilla and P. aduncum showed enzyme inhibition zone in amounts of 0.01 ng and 1ng, respectively. The oil of P.marginatum showed weak activity (~ 100 ng) and the oils of P. callosum and P. divaricatum were inactive. Among the major constituents, who showed activity are the phenylpropanoids 1-nitro-2-phenylethane, isolated from the oil of A. canelilla, and safrole and elemicin, isolated from the oil of P. callosum, which inhibited the AChE in amounts of 0.01, 1000 to 1000 ng, respectively. The results indicate that the oil of A. canelilla and 1-nitro-2-phenylethane inhibited AChE in the same proportion as the pattern physostigmine. The molecular docking study was added to the experimental results, showing that the nitro group of 1-nitro-2-phenylethane can establish hydrogen bonds with the hydroxyl group of the serine residue existing in the catalytic AChE molecule, suggesting that the electronegative character of 1-nitro-2-phenylethane may be responsible for this strong chemical interaction.